2018
DOI: 10.1038/s41396-018-0303-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic imprint of woody plants on the soil mycobiome in natural mountain forests of eastern China

Abstract: Recent studies have detected strong phylogenetic signals in tree-fungus associations for diseased leaves and mycorrhizal symbioses. However, the extent of plant phylogenetic constraints on the free-living soil mycobiome remains unknown, especially at broad geographic scales. Here, 343 soil samples were collected adjacent to individual tree trunks, representing 58 woody plant species located in five mountain forests of eastern China. Integrating plant species identity and phylogenetic information, we aimed to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
57
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 91 publications
11
57
3
Order By: Relevance
“…By disentangling the individual and joint influences of host phylogeny, abiotic conditions and spatial proximity on the assembly of PF and MF communities, we found that the independent effects of host phylogeny accounted for > 60% of the explained variation in richness and composition for both fungal guildsat least three times that of any other single factor, or their interactions. The strong effects of host phylogeny on MF relative to other factors coincides with previous studies conducted on a wide phylogenetic range of plants van der Linde et al, 2018;Yang et al, 2019), yet conflicts with studies involving more closely related plant species (Morris et al, 2008;Glassman et al, 2017). Our finding that the effect of host phylogeny on MF increased at a larger phylogenetic scale to a greater extent than in PF (Fig.…”
Section: Host Phylogeny Dominates the Variation In Fungal Community Rsupporting
confidence: 65%
See 2 more Smart Citations
“…By disentangling the individual and joint influences of host phylogeny, abiotic conditions and spatial proximity on the assembly of PF and MF communities, we found that the independent effects of host phylogeny accounted for > 60% of the explained variation in richness and composition for both fungal guildsat least three times that of any other single factor, or their interactions. The strong effects of host phylogeny on MF relative to other factors coincides with previous studies conducted on a wide phylogenetic range of plants van der Linde et al, 2018;Yang et al, 2019), yet conflicts with studies involving more closely related plant species (Morris et al, 2008;Glassman et al, 2017). Our finding that the effect of host phylogeny on MF increased at a larger phylogenetic scale to a greater extent than in PF (Fig.…”
Section: Host Phylogeny Dominates the Variation In Fungal Community Rsupporting
confidence: 65%
“…Differences in the factors determining ECM fungal communities have also been demonstrated (e.g. Tedersoo et al ., ; Yang et al ., vs Morris et al ., ; and Glassman et al ., ). In our study, the total contribution of the environment and space did not account for > 27% of explained variation in the richness or community composition of either guild, consistent with Tedersoo et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A previous study showed that patchy species aggregation in bulk soil might lead to divergent composition of communities (Faust & Raes, ). Species competition–cooperation trade‐offs might also have shifted with changes in availale nutrients in the rhizosphere (Yang et al, ), leading to variation in community composition within the local scale (Chesson & Huntly, ; Kneitel & Chase, ; Tilman, ). Third, sampling across the whole region might not have contributed to significant increases in bacterial diversity above what was already observed at the local scale.…”
Section: Discussionmentioning
confidence: 99%
“…Tedersoo et al (2014) reported that soil fungal community composition could be best predicted by climatic, edaphic and floristic factors at the global scale. Similarly, Yang et al (2019) proposed that abiotic environmental filtering was the dominant driving force on soil fungal biogeography even after considering the effects of biotic interaction. Table 1 The proportion of the lowest Akaike information criterion (AIC) value for six species rank abundance distribution models of fungal communities on the local scale and regional scale.…”
Section: Deterministic Processes Govern the Assembly Of Soil Fungal Cmentioning
confidence: 99%